Proceedings of the 11th International Toki Conference on Plasma Physics and Controlled Nuclear Fusion (ITC-11), 5th-8th December, Toki-city, Japan - International Toki Conference on Plasma Physics and Controlled Nuclear Fusion (ITC-11) (11th : 2000 : Japan); The Japan Society of Plasma and Nuclear Fusion Research (Nagoya, Japan : The Japan Society of Plasma Science and Nuclear Fusion Research, 2001)
40